REPRESENTASI PEREMPUAN KARIER INDONESIA PADA ERA 70-AN DAN ERA MODERN (Analisis Semiotika Pada Cover Majalah Femina edisi tahun 1972 dan tahun 2012): REPRESENTATION OF INDONESIAN CAREER WOMEN IN THE 70’S ERA AND THE MODERN ERA (Semiotic Analysis on Femina Magazine 1972 and 2012 edition) - Anastasia Ari Respati (Universitas Trisakti, 2024)
Career women is the subject of conversation which appointed by the UN since the 70’s, as well as in Indonesia, which signed an agreement with the UN. Since 1978, the role of women in professional careers began to appear, both in private companies and government agencies, so that the role of women’s careers was changing. This changing was recorded in the mass media as a recording tool for any eras, through two samples of Femina magazine cover shown changes in the representation of Indonesian women’s career in the late 70s and the modern era. Both the cover of Femina magazine examined using semiotic analysis by Roland Barthes, to find meaning denotative, connotative and myths of women's career behind the making of the cover at the time of publication. With a constructivist qualitative methods, the social construction that forms the changing of Indonesian women's careers representation can be seen in more detail. In this study it was shown that in the 70’s, role of Indonesian women’s career is very strong seen in the domestic sphere, while in the modern era, representation of careeer woman in Indonesia is more viscous as a professional who has a career in the world of work outside the home. The time changes, especially the changes of the economy and the education system in Indonesia which took Indonesian women to the familiar liberal feminism, where Indonesian career women have equal opportunities with men to occupy important positions in both private companies and government agencies.